Culture in the Internet era: changing value orientations - Машталер, А.А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The paper analyzes the problem of the crisis of culture in the era of the information society. The author argues that the present state of culture is its logical step, which causes a change of thinking, being, values. This is the meaning of innovation.